Variations in the Presentation of Aphasia in Patients with Closed Head Injuries - Dara Oliver Kavanagh; Conor Lynam; Thorsten Düerk; Mary Casey; Paul W. Eustace (Case Reports in Medicine)
Impairments of speech and language are important consequences of head injury as they compromise interaction between the patient and others. A large spectrum of communication deficits can occur. There are few reports in the literature of aphasia following closed head injury despite the common presentation of closed head injury. Herein we report two cases of closed head injuries with differing forms of aphasia. We discuss their management and rehabilitation and present a detailed literature review on the topic. In a busy acute surgical unit one can dismiss aphasia following head injury as behaviour related to intoxication. Early recognition with prolonged and intensive speech and language rehabilitation therapy yields a favourable outcome as highlighted in our experience. These may serve as a reference for clinicians faced with this unusual outcome.